THE EFFECTS OF HONEY ADMINISTRATION ON SOLUABLE FMS-LIKE TYROSINE KINASE (SFLT-1), SOLUBLE ENDOGLIN (S-ENG), VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) SERUM LEVELIN THE RAT MODEL OF PREECLAMPSIA - ASROEL, EDWIN MARTIN; MAAT, SOEPRAPTO; SITEPU, MAKMUR; ILYAS, SYAFRUDDIN (International Journal of Current Pharmaceutical Research, 2020)
Objective: To find out the effect of honey administration on changes in antiangiogenic and proangiogenic serum levels in the rat model of preeclampsia. This study is the first research that examines the effect of honey on preeclampsia especially on proangiogenic and antiangiogenic factors Methods: This study uses analytic research with a quasi-experimental design in laboratory rats (Rattus Norvegicus) pregnant females given honey with concentration. The treatment of all samples was carried out simultaneously and during the treatment it was observed using the type of postest only control group design. Results: Honey administration significantly reduced sFlt-1 levels in preeclampsia rats, and a greater dose of honey had an effect on strengthening the effect of honey in reducing sFlt-1 levels. Honey administration significantly increased VEGF levels in preeclampsia mice (p = 0.034). Honey administration significantly decreased s-Eng levels in preeclampsia mice, and administration of a larger dose of honey had an effect on strengthening the effect of honey in reducing s-Eng levels (p = 0.012). Conclusion: The honey administration on rat’s model of preeclampsia may reduce the antiangiogenic level sFlt-1 and sEng dan increase VEGF level as the pro-angiogenic